If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(9x + 5) = 12x + -2 Reorder the terms: 2(5 + 9x) = 12x + -2 (5 * 2 + 9x * 2) = 12x + -2 (10 + 18x) = 12x + -2 Reorder the terms: 10 + 18x = -2 + 12x Solving 10 + 18x = -2 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 10 + 18x + -12x = -2 + 12x + -12x Combine like terms: 18x + -12x = 6x 10 + 6x = -2 + 12x + -12x Combine like terms: 12x + -12x = 0 10 + 6x = -2 + 0 10 + 6x = -2 Add '-10' to each side of the equation. 10 + -10 + 6x = -2 + -10 Combine like terms: 10 + -10 = 0 0 + 6x = -2 + -10 6x = -2 + -10 Combine like terms: -2 + -10 = -12 6x = -12 Divide each side by '6'. x = -2 Simplifying x = -2
| x-7+3x=18 | | -95.552=-3.2(3.2n+6.5) | | 3x+75=360 | | -2a+15-4b= | | 2a+15-4b= | | x+31+29=90 | | Y=3.4x-0.2 | | 8(x+5)=2(4x+1)+38 | | 725=15n+5 | | 26=7x+6-(-3x) | | 2x+128=180 | | 8(3x-7)=2(12x+8) | | A*6+4=14 | | 2g^3h^3/14g | | 88/3-8 | | 14+7a=28 | | 32-8/3 | | 9x/x^2 | | x^2+7x+44= | | (x-7)*7=6x-6 | | 2(4x-1)=3(x+2)+5 | | f(-4)=4x-2 | | 65327=.8x | | c=24n+4 | | 6(x-11)=15-14x | | 6x+6x+2+7=4x+5+7x | | 3x-1/x-4 | | 460=24n+4 | | 6y-2(y+1)=(y-2)+6 | | 7x+11=3(x+y) | | (3d)(3d)(d-7)=0 | | X+(X*0.75)=608 |